Development narratives in a post-aid era: Reflections on implications for the global effectiveness agenda - Nilima Gulrajani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper argues that the crisis facing the development effectiveness agenda is fundamentally derived from limited collective commitment to a singular model of development, one where a developed North serves as model and funder for a developing South. This is partly the reason for the lacklustre political support received by the Global Partnership for Effective Development Cooperation (GPEDC) that emerged from the 2011 Busan High Level Forum. The discrediting of this North/South binary and the arrival of an era of multistakeholder-ism has generated a pluralism of development narratives better suited to 21st century geographies and global challenges. In this paper, I unpack three of these narratives, each framed by either supranational, nationalist, and solidaristic understandings of development. Building a political consensus around development effectiveness requires, as a first step, an awareness of these alternative framings of what global development currently stands for, including its objectives, modalities, financing channels, and stakeholders. This analysis foregrounds the ways each narrative holds different sets of actors accountable for conforming to effectiveness principles and empowers distinctive rights holder to hold these duty bearers to account. How far narrative pluralism can be accommodated within the universalist logic of development effectiveness remains to be seen.
Keywords: 330; development effectiveness; foreign aid; North South; international cooperation; global public goods; global public investment; nationalism